2015
DOI: 10.1177/0272989x15583845
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Cost-effectiveness of Interventions That Affect Fertility and Childbearing

Abstract: Background Current guidelines for economic evaluations of health interventions define relevant outcomes as those accruing to individuals receiving interventions. Little consensus exists on counting health impacts on current and future fertility and childbearing. Objective To characterize current practices for counting such health outcomes. Design We developed a framework characterizing health interventions with direct and/or indirect effects on fertility and childbearing and how such outcomes are reported.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 124 publications
2
43
0
Order By: Relevance
“…Methodological challenges especially related to the choice and valuation of outcomes can make cost-effectiveness results biased and those should be interpreted with caution. 13,35 Those challenges are mostly related on the choices of time horizon and health outcomes. Ideally, if we strictly follow guidelines of economic evaluation, 36 a wellconducted economic evaluation should consider a time horizon enough to capture all relevant health outcomes and costs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Methodological challenges especially related to the choice and valuation of outcomes can make cost-effectiveness results biased and those should be interpreted with caution. 13,35 Those challenges are mostly related on the choices of time horizon and health outcomes. Ideally, if we strictly follow guidelines of economic evaluation, 36 a wellconducted economic evaluation should consider a time horizon enough to capture all relevant health outcomes and costs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, economic evaluation of a prenatal intervention such as screening and diagnosis has also to capture all relevant costs and outcomes within a pregnancy, but also over a long time horizon enough to capture future health outcomes and the economic impact of an intervention. 13,35 Even if most women opt for pregnancy termination after confirmation of aneuploidy diagnosis, it is important to consider also long-term horizon in order to measure consequences related to treatment and management of cases born alive (ie, those not detected by prenatal screening and those whose mothers declined the termination of pregnancy) which include the costs outside the health care system that are difficult to assess. Regarding the health outcomes measures in economic evaluation of screening for aneuploidy, our review found that there were a variety of outcomes used, mostly, the number of DS/aneuploidy detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the concept of HRQoL is applicable to all patient populations and health states, the transient nature of pregnancy may require a different conceptual model [32,33] than that used for chronic diseases like cancer and diabetes that have extensive research literature regarding assessment of HRQoL. Further testing with domain specific PROMIS measures (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, short‐term outcomes may be based on primary data, whereas long‐term effects are often extrapolated. Time horizons considered by CDA studies in perinatology include “pregnancy and delivery”, “pregnancy and the postpartum period” (variably, 6 weeks to 1 year), “the mother's reproductive life” and maternal lifetime for maternal outcomes and anything between a few months after birth to the entire lifetime for offspring outcomes . Caution must be exercised while considering short time horizons such as pregnancy and delivery alone, as the implications of some interventions and outcomes extend beyond that time horizon.…”
Section: Considerations Specific To Perinatologymentioning
confidence: 99%